Comparison of the effect of electronic education and workshop on the satisfaction of nurses about Emergency Severity Index triage - Ahmadreza Yazdannik; Shahla Mohamadirizi; Mohammad Nasr-Esfahani (Wolters Kluwer Medknow Publications, 2020)
INTRODUCTION: Nurse educators need to develop the level of scientific and practical of the students with the goal of becoming expert nurses. However, the use of modern educational methods to raise the motivation and satisfaction of learners can help individuals achieve this goal. Therefore, the aim of this study was to investigate the effect of health education in emergency nurses about triage. METHODS: A two-group pool-blind experimental study was performed on seventy emergency nurses. Samples were randomly assigned into two groups: e-learning group (35 individuals = electronic education) and traditional group (35 = workshop education). The demographic questionnaire and the satisfaction questionnaire before and 2 weeks after the intervention in both groups were completed. RESULTS: Independent t-test showed that the satisfaction scores before intervention in both e-learning and traditional groups were not statistically significant, whereas there was a significant difference between two groups after 2 weeks after the intervention (P = 0/015). CONCLUSION: Using nursing professors' electronic education programs can increase the level of satisfaction and motivation in the nursing mothers. Therefore, the use of this new educational method is recommended by managers and educational planners as an effective teaching.